Penggunaan Media PACAPI yang Diterapkan Melalui Pendekatan PMRI pada Materi Pecahan - Ansyah, Mukhammad Hendry; Albab, Ahmad Ulil; Zuliana, Eka (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This study aims to provide a comprehensive description of the use of the PMRI (Indonesian Realistic Mathematics Education) approach assisted by the PACAPI (Pizza Fraction Board) teaching media. The subjects of this study were 24 third-grade students of SD 4 Dersalam, located in Dersalam Village, Bae District, Kudus Regency. This study used a qualitative method with a case study approach. The research subjects, totaling 24 people, were selected using purposive sampling techniques. Data collection techniques in this study included observation, interviews, and documentation. The data analysis technique used was qualitative data analysis with the stages of data reduction, data presentation, and drawing conclusions. The analysis results show that this PMRI approach provides a strong foundational concept to the students. Students begin to think about anything related to the topic of fractions. Then, they show a strong desire to participate, not only listening attentively but also being eager to answer questions. Finally, when solving problems, students are able to use symbols without using teaching media.